A nonlinear rate-dependent model for predicting the depth of penetration in ultra-high performance fiber reinforced concrete (UHPFRC). (February 2020) - Cao, Y.Y.Y.; Tan, Q.H.; Jiang, Z.G.; Brouwers, H.J.H.; Yu, Q.L.
Abstract: Ultra-high performance fiber reinforced concrete (UHPFRC) is increasingly utilized in protective structures because of its ultra-high compressive strength and excellent toughness. Nevertheless, there is still a lack of model for predicting the depth of penetration (DOP) in UHPFRC against projectile penetrations. This study proposes an analytical predicting model for UHPFRC on the basis of the dynamic cavity expansion theory. The Hoek-Brown criterion is utilized to account for the nonlinear response of UHPFRC, and its rate dependency is also addressed in the model. The developed predicting model is validated against penetration experimental data, and its effectiveness is further compared with previous predicting formulae. The comparison results indicate that the proposed model can achieve more reasonable DOP predictions in UHPFRC targets. Finally, a number of influential parameters are discussed based on the proposed model. It is observed that the DOP is affected by the target compressive strength, while the tensile strength influences the cracked region radius. The developed DOP predicting model provides an accurate estimation of the UHPFRC impact resistance and promotes an effective approach to design UHPFRC protective structures.